DNA metabarcoding of non-fungal eukaryotic diversity in air and snow of Livingston Island, South Shetland Islands, Antarctica - Câmara, Paulo E.A.S.; Šantl‑Temkiv, Tina; Pinto, Otavio H.B.; Convey, Peter; Dall’Osto, Manuel; Bones, Fabio L.V.; Carvalho-Silva, Micheline; Henriques, Diego Knop; Rosa, Luiz Henrique (Polar research, 2025)
A major natural route of dispersal to Antarctica is often assumed to be atmospheric transport, although few studies have documented this in detail. Aerial dispersal to Antarctica is very challenging as the continent is geographically remote from other land areas and is isolated by the atmospheric circumpolar vortex. Detailed information about aerial routes by which microorganisms arrive and circulate in Antarctica is generally lacking, as few aerobiological studies have focused on eukaryotes and those that have predominantly relied on traditional morphological identification. Recent advances in molecular biology, such as DNA metabarcoding by high throughput sequencing (HTS), have provided a powerful new tool for the study of atmospheric biological diversity and can retrieve levels of diversity an order of magnitude higher than traditional methods. In this study, we used HTS to investigate the diversity of non-fungal eukaryotes present in the atmosphere and freshly precipitated snow on Livingston Island. In a total of 740 m3 of air and 3.76 L of snow sampled, representatives of four kingdoms (Protozoa, Chromista, Viridiplantae and Animalia) and five phyla (Ciliophora, Ochrophyta, Chlorophyta, Magnoliophyta and Porifera) were found. The most diverse phylum was Chlorophyta, represented in our samples by 10 taxa, with Trebouxia asymmetrica Friedl & Gärtner the most abundant representative.